AVTOMOBIL BENZINLERІNІŃ EKOLOGIYALÍQ QASIҮETLERІNE HÁR QÍYLÍ FUNKCIONALLÍ QOSPALARDÍŃ TÁSIRІ M.J.Maxmudov- ximiya ilimleriniń doktorı, dotsent Buxara injenerlik-texnologiya institutı - Ametova, D.M. (SCIENCE and SOCIETY, 2021)
The growth of the car park and the associated increase in environmental pollution impose more and stringent requirements on the quality of the produced gasoline’s, in particular, their environmental properties. The article presents the characteristics of additives that improve the environmental and anti-knock properties of motor gasoline’s and their degree of influence in local gasoline’s.